Development of novel cyclic NGR peptide–daunomycin conjugates with dual targeting property - Tripodi, Andrea Angelo Pierluigi; Tóth, Szilárd; Enyedi, Kata Nóra; Schlosser, Gitta; Szakács, Gergely; Mező, Gábor (Beilstein Journal of Organic Chemistry, 2018)
Cyclic NGR peptides as homing devices are good candidates for the development of drug conjugates for targeted tumor therapy. In our previous study we reported that the Dau=Aoa-GFLGK(c[KNGRE]-GG-)-NH2 conjugate has a significant antitumor activity against both CD13+ HT-1080 human fibrosarcoma and CD13− but integrin positive HT-29 human colon adenocarcinoma cells. However, it seems that the free ε-amino group of Lys in the cycle is not necessary for the biological activity. Therefore, we developed novel cyclic NGR peptide–daunomycin conjugates in which Lys was replaced by different amino acids (Ala, Leu, Nle, Pro, Ser). The exchange of the Lys residue in the cycle simplified the cyclization step and resulted in a higher yield. The new conjugates showed lower chemostability against deamidation of Asn than the control compound, thus they had lower selectivity to CD13+ cells. However, the cellular uptake and cytotoxic effect of Dau=Aoa-GFLGK(c[NleNGRE]-GG-)-NH2 was higher in comparison to the control especially on HT-29 cells. Therefore, this conjugate is more suitable for drug targeting with dual targeting property.
Keywords: antitumor activity; drug release; NGR peptides; oxime-linkage; targeted drug delivery